Features of the Development and Support of Personal Resilience in War Conditions - Рrykhodko, D.; Кyslyi, V. (ХДАК, 2024)
Humanity living in the modern world is constantly testing its resilience. The population of Ukraine is also experiencing the growing intensity of social change, an increase in the amount of information, crises in society, the economy and politics, and the need to get used to technological innovations. In addition, each person faces personal challenges that can test their resilience. The harmful impact of these factors on the people of Ukraine has been exacerbated by the COVID-19 pandemic and the terrible consequences of the war in the course of Russia’s full-scale armed aggression. All of these factors cause tension, increase stress and have a negative impact on a person’s mental health. The negative impact on the individual’s psyche is manifested by neurotic disorders, depression, and behavior that deviates from the norms and rules accepted in society.
Keywords: резильєнтність особистості